Surface electromyographic analysis of the common strengthening exercises for the vastus medialis and vastus lateralis muscles - Nordin, Simbak; Naresh Bhaskar, Raj; Nor Azizah, Hussin; Mohd Khairuddin, Mohd Safee (2017)
This study was done to identify strengthening exercises that elicit the greatest level of EMG activity in the vastus medialis and vastus lateralis muscles. Strengthening exercises are important to improve muscle power. The vastus medialis and vastus lateralis muscles are important for knee function. Reduced muscle power of vastus medialis and vastus lateralis muscles causes instability of knee and abnormal knee biomechanics. Little information exists on the EMG activity of vastus medialis and vastus lateralis muscles during common strengthening exercises. This study, therefore, was designed to compare electromyographic data obtained from the vastus medialis and vastus lateralis muscles during static quadriceps exercise, inner range quadriceps exercise and straight leg raise exercise. Fifty healthy subjects, aged 20-21 years (35 females and 15 male) were recruited. Surface electrodes recorded EMG activity of the vastus medialis and vastus lateralis muscles during static quadriceps exercise, inner range quadriceps and straight leg raise. The normalized electromyographic muscle data were analysed using Repeated Measure ANOVA (p ≤ 0.05). The inner range quadriceps exercise was found to produce the greatest EMG activity in the vastus lateralis muscle. For the vastus medialis muscle, the greatest EMG activity was observed during inner range quadriceps exercise rather than static quadriceps exercise and straight leg raise exercise. This study identified that inner range quadriceps exercises maximally activated the vastus medialis and vastus lateralis muscles. This information may be helpful for clinicians in developing and prescribing exercise programs for patients with musculoskeletal disorders.